Pengembangan Website Sekolah sebagai Media Promosi dan Informasi Berbasis Digital - Nugroho, Agung; Surojudin, Nurhadi; Maulana, Donny; Romli, Ikhsan (Cahaya Pengabdian, 2025)
This community service program aims to overcome the limitations of promotional and informational media at SMP Negeri 1 Cikarang Timur through the development of a digital-based school website. Until now, the dissemination of information and promotion has relied on conventional media, which are ineffective and inefficient, thereby hindering accessibility and the school's image. Using a qualitative-participatory approach, the community service team conducted a needs analysis, design, development, and implementation of the website using the WordPress Content Management System (CMS). The results of this activity show that the developed website successfully functions as an integrated information center and effective promotional media. It is hoped that this website will continue to provide long-term benefits in supporting information transparency and increasing the school's competitiveness in the digital era